2019
DOI: 10.2140/pjm.2019.300.499
|View full text |Cite
|
Sign up to set email alerts
|

Towards a sharp converse of Wall’s theorem on arithmetic progressions

Abstract: Wall's theorem on arithmetic progressions says that if 0.a1a2a3 . . . is normal, then for any k, ℓ ∈ N, 0.a k a k+ℓ a k+2ℓ . . . is also normal. We examine a converse statement and show that if 0.an 1 an 2 an 3 . . . is normal for periodic increasing sequences n1 < n2 < n3 < . . . of asymptotic density arbitrarily close to 1, then 0.a1a2a3 . . . is normal. We show this is close to sharp in the sense that there are numbers 0.a1a2a3 . . . that are not normal, but for which 0.an 1 an 2 an 3 . . . is normal along … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Weiss and Kamae ([18] and [10]) showed that a number is normal if and only normality is preserved along every deterministic subsequence with positive asymptotic lower density. In a recent work, Vandehey [16] proved a nearly sharp converse to the Wall's theorem. Vandehey considers collections of subsequences such that for any ǫ, the collection contains a subsequence with asymptotic lower density greater than 1 − ǫ. Theorem 1.3 in [16] shows that preservation of normality along all subsequences in such a collection implies the normality of the original number.…”
Section: Lemma 19 Follows Using Dimmentioning
confidence: 97%
See 2 more Smart Citations
“…Weiss and Kamae ([18] and [10]) showed that a number is normal if and only normality is preserved along every deterministic subsequence with positive asymptotic lower density. In a recent work, Vandehey [16] proved a nearly sharp converse to the Wall's theorem. Vandehey considers collections of subsequences such that for any ǫ, the collection contains a subsequence with asymptotic lower density greater than 1 − ǫ. Theorem 1.3 in [16] shows that preservation of normality along all subsequences in such a collection implies the normality of the original number.…”
Section: Lemma 19 Follows Using Dimmentioning
confidence: 97%
“…In a recent work, Vandehey [16] proved a nearly sharp converse to the Wall's theorem. Vandehey considers collections of subsequences such that for any ǫ, the collection contains a subsequence with asymptotic lower density greater than 1 − ǫ. Theorem 1.3 in [16] shows that preservation of normality along all subsequences in such a collection implies the normality of the original number. Theorem 1.4 from the same paper shows that this converse to the Wall's theorem is close to being sharp.…”
Section: Lemma 19 Follows Using Dimmentioning
confidence: 97%
See 1 more Smart Citation